Utilization of red dwarf santan (Ixora coccinea Lin.) flowers in candy making. - Seguera, Caitline Keigh Apostol (2018.)
Ixora coccinea Linn. flower or locally known as santan flower was proven to have pharmacological properties that were evaluated and proven to treat different kinds of ailments. The physico-chemical properties of flowers were characterized in terms of its pH level, titrable acidity and total soluble acids. The flowers were measured to have a pH level of 3.78, titrable acidity of 2.11% ursolic acid, TSS value of 5.33 and 31.33°Brix for flowers and nectar, respectively.The flowers of santan plant were utilized in candy making to determine its potential for product development. The santan candy product was subjected to physico-chemical and proximate analysis as well as its sensorial attributes. The physico-chemical properties of santan candy was evaluated to have pH level of 3.89, titrable acid of 0.31% ursolic acid, TSS value of 37.50°Brix water activity of 0.49, textural hardness of 416.45N and calorie value of 234.28kcal per 100g. The proximate composition of santan candy was determined to have a 0.16% moisture, 0.26% crude proximate composition of santan candy was determined to have a 0.16% moisture, 0.26% crude ash, ≤1.0x10-60% crude fat, 0.57% crude fiber, 0.16% crude protein and 98.85% carbohydrates. The product was perceived to have the highest amount of carbohydrates due to its sucrose content.The santan candy was perceived as light red in color, moderately sweet taste, slight santan flavour and odor and smooth surface texture. Sensory evaluation was conducted among three different age groups consisting of employees, students and kids. Overall rating of the product was perceived to be like very much. Thus, indicates that santan candy has high probability for commercialization.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Santan flower; Ixora coccinea Linn; Santan candy making